Mengoptimalkan Akuntabilitas dalam Manajemen Bimbingan dan Konseling: Tantangan, Analisis, dan Solusi - Wiyul Fitrhi, Titik; firman, Firman; Yarni, Nevi (Journal of Educational Management and Strategy, 2024)
The development of student input at SMKN 1 Bukittinggi is rapid, so it requires attention to managing student development at school through optimizing school guidance management. This study aims to optimize the accountability of guidance and counseling management through identifying challenges and analyzing the implementation of guidance and counseling management accountability at SMKN 1 Bukittinggi, as well as offering innovative solutions that can be applied to overcome these challenges. This research uses a qualitative approach with a descriptive study design at SMKN 1 Bukittinggi. The informants of this research are the head and vice headmaster, guidance and counseling coordinator, guidance and counseling teacher, teacher council and students of SMKN 1 Bukittinggi using purposive method. Data collection methods using interview guidelines, observation and documentation. The method of data analysis was descriptive analysis. The results revealed that the main challenges faced include the lack of independent standard operating procedures, limited resources, limited use of technology in monitoring and evaluating BK services and the organization of BK supervision from the education office is still rare. To overcome these challenges, the study recommends several solutions, including the development of clear accountability standards, increasing the capacity of professionals and integrating technology in the monitoring and evaluation process. The implications of the research offer practical and innovative approaches that can be applied by practitioners and policymakers to improve the accountability of BK management. Abstrak Perkembangan input siswa SMKN 1 Bukittinggi kiat pesat, sehingga membutuhkan perhatian pengolalan perkembangan siswa disekolah melalui pengoptimalan manajemen bimbingan disekolah. Penelitian ini bertujuan untuk mengoptimalkan akuntibilitas manajemen bimbingan dan konseling melalui tindakan mengidentifikasi tantangan dan analisis penerapan akuntabilitas manejemen bimbingan dan konseling (BK) di SMKN 1 Bukittinggi, serta menawarkan solusi inovatif yang dapat diterapkan untuk mengatasi tantangan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskritif studi di SMKN 1 Bukittinggi. Infoman penelitian ini yakni kepala dan wakil kepala sekolah, koordianator BK, Guru BK, majelis Guru dan siswa SMKN 1 Bukittinggi dengan menggunakan metode purposive. Metode pengumpulan data menggunakan pedoman wawancara, observasi dan dokumentasi. Metode analisis data dengan melakukan analisis deskriftif. Hasil penelitian mengungkap tantangan utama yang dihadapi meliputi kurangnya standar operasional prosedur mandiri, keterbatasan sumber daya, penggunaan teknologi dalam pemantauan dan evaluasi layanan BK terbatas dan penyelenggaraan pengawasan BK dari dinas pendidikan masih jarang dilakukan. Untuk mengatasi tantangan ini, penelitian ini merekomendasikan beberapa solusi, antara lain pengembangan standar akuntabilitas yang jelas, peningkatan kapasitas tenaga profesional, dan integrasi teknologi dalam proses pengawasan dan evaluasi. Implikasi penelitian menawarkan pendekatan praktis dan inovatif yang dapat diterapkan oleh praktisi dan pembuat kebijakan untuk meningkatkan akuntabilitas manajemen BK.